Report of the survey of opinions on the Irrigation Research Management Unit - Abeyewardene, A.; Brewer, J.D. (International Irrigation Management Institute, 1997)
The results are presented of a questionnaire survey of 42 IRMU staff and other related personnel which was conducted between February and April 1996. The main subjects covered were: research areas covered by IRMU; appropriateness of IRMU structure and organizations to fulfil these roles; the performance and effectiveness of technical assistance of IRMU; and the future of IRMU.